Atividade física e pressão arterial em crianças obesas - Everton de Freitas, André (2016)
This study aimed to evaluate the chronic effect of an exercise program in resting blood pressure values of school children aged six to nine years old with overweight and obesity in public schools of the city of OuroPreto, Minas Gerais - Brazil, comparing the systolic and diastolic blood pressure of these students before and after an intervention program. Method: This is a randomized clinical study of intervention, quasi-experimental, double-blind, pragmatic, with the study of the individual unit. Seventy-nine children participated in the interventional study and were considered a convenient sample. These subjects were allocated by randomization into two groups: the intervention group (n = 40) and the control group (n = 39) practised physical activity three times a week for 50 minutes and were followed for 4 months. The exercise intensity was determined by open-circuit spirometry. Blood pressure was measured three times consecutively and the average was used. Results: After the intervention, there was no evidence of significant chronic effects of a regular program of exercises on basal levels of blood pressure of obese children between 6 and 9 years old. Conclusion: In this study, there was no evidence of significant effects from a program of regular physical activity on basal levels of blood pressure of obese children between 6 and 9 years old.